Social Media Fiqh: Social Media Use Intensity and Family Harmony in Tulungagung Regency - Muhammad Ngizzul Muttaqin; Iffatin Nur; Ahmad Muhtadi Anshor (The Journal of Society and Media, 2022)
The use of social media by women is oftentimes understood as a detriment to family sustenance. As a result, the stigmatization of social media user and social media misuse aspects is often associated with women. In addition, in family structures, men hold a very strong position. The men’s authority then has implications for the control and intervention against their wives in the use of social media. Based on this phenomenon, this qualitative study with a case study on women's activities on social media in Tulungagung Regency aimed to formulate an ijtihad model of the fiqh of social media with maqashid sharia and social reality as the basis. The findings of this study show that: 1. The intensity of women’s activities in social media in Tulungagung Regency, in essence, is adjusted to the needs and goals in the use of social media, 2. Women’s activities in social media in Tulungagung Regency, in essence, has implication for creating harmony in the family, 3. Women’s activities in social media in Tulungagung, in essence, is an actualization of social media fiqh, and 4. The implications of women’s social media activities in Tulungagung are the embodiment of social media fiqh.